Water surge risk mapping using GIS-based spatial multi-criteria decision analysis approach - Syarifuddin, Misbari (IOP Science, 2025)
Water surge is a frequent natural disaster in Malaysia, with about 186 areas nationwide identified as being at risk. The absence of an updated water surge risk map for recreational areas has led to numerous deaths, property damage, and environmental destruction. Lack of assessment of the physical environment using geospatial technology towards water surge occurrence has led to less effective disaster management and mitigation strategies related to water surge in recreational areas. The aim of this study is to develop a recent water surge risk map using geospatial technology, with a focus on a recreational area in Pahang, Malaysia. The process entails gathering geographical data and evaluating data using GIS-based Spatial Multi-Criteria Decision Analysis (SMCDA), which is generally based on the Analytic Hierarchy Process (AHP) model in ArcGIS Pro. A water surge risk map is developed by not only visualizing water surge factors but also weighting each relevant contributing factor, such as terrain elevation, land use type, and rainfall. The finding of the study suggests that Sg. Pandan Waterfall area falls into medium-risk water surge zones due to combination of three main factors including terrain elevation, land use or rainfall pattern. The map is crucial to enhancing resource allocation, disaster planning, and community resilience where water surges have not previously been mapped. This study not only helps in raising awareness about water surge risks but also supports SDG 14 and SDG 15 initiatives as well as building safe communities.